Carbohydrate recognition by boronolectins, small molecules, and lectins - Shan Jin; Yunfeng Cheng; Suazette Reid; Minyong Li; Binghe Wang (2009)
Abstract Carbohydrates are known to mediate a large number of biological and pathological events. Small and macromolecules capable of carbohydrate recognition have great potentials as research tools, diagnostics, vectors for targeted delivery of therapeutic and imaging agents, and therapeutic agents. However, this potential is far from being realized. One key issue is the difficulty in the development of “binders” capable of specific recognition of carbohydrates of biological relevance. This review discusses systematically the general approaches that are available in developing carbohydrate sensors and “binders/receptors,” and their applications. The focus is on discoveries during the last 5 years. © 2009 Wiley Periodicals, Inc. Med Res Rev, 30, No. 2, 171–257, 2010